بناء مقياس متعدد الأبعاد في تقدير الذات - النعيمات، خالد; السرور، ناديا هايل (الجامعة الأردنية - عمادة البحث العلمي, 2018)
هدفت هذه الدراسة إلى بناء مقياس متعدد الأبعاد في تقدير الذات للأفراد ممن هم في المدى العمري (13 – 18) سنة، والتحقق من خصائصه السيكومترية، وتحري الفروق في أبعاد تقدير الذات تبعاً لمتغير النوع الاجتماعي والعمر والمنطقة الجغرافية، تكونت عينة الدراسة من (1008) طالباً وطالبة من طلبة المدارس الحكومية التابعة لوزارة التربية والتعليم في الأردن، من الصف السابع إلى الصف الثاني عشر (الثاني ثانوي). تم بناء مقياس تقدير الذات متعدد الأبعاد بعد الاطلاع على المقاييس المنشورة المتعلقة بسمة تقدير الذات، وتم التطبيق على عينة الدراسة، وتم التحقق من صدق المقياس من خلال تحكم الفقرات من قبل محكمين مختصين، كما وكتم التحقق من صدق البناء من خلال إجراء التحليل العاملي من الدرجة الأولى والثانية، حيث أظهرت نتائج التحليل العاملي من الدرجة الثانية وجود خمسة عوامل هي: تقدير الذات الأكاديمي، تقدير الذات العائلي، تقدير الذات الاجتماعي، تقدير الذات الشخصي، وتقدير الذات الرفاقي، كما تم إجراء الصدق المرتبط بالمحك باستخدام مقياس روزنبيرج لتقدير الذات حيث كان معامل ارتباط بيرسون بينهما (0.79)، وتم التحقق من ثبات المقياس وأبعاده من خلال الاتساق الداخلي بطريقتي معامل كرونباخ ألفا (α)، والتجزئة النصفية، بالإضافة إلى ثبات تباعد الأفراد وتباعد الفقرات، وكانت قيم الثبات جيدة حيث تراوحت بين (81. – 64.). لتحري الفروق في أبعاد تقدير الذات تبعاً لمتغير النوع الاجتماعي، العمر والمنطقة الجغرافية عند مستوى دلالة إحصائية (α = 0.05)، وتم استخدام تحليل التباين المتعدد (MANOVA)، وتبين أن هناك فروق ذات دلالة إحصائية عند مستوى دلالة (α = 0.05) تبعاً لمتغير العمر الممثل بالصف بين الصف السابع والصف الثامن في بعد تقدير الذات الأكاديمي لصالح الصف السابع، بينما كان هناك فروق ذات دلالة إحصائية عند مستوى دلالة (α = 0.05) في أبعاد تقدير الذات (العائلي، الشخصي، الرفاقي) تبعاً للمنطقة الجغرافية الممثلة بالأقليم.
The main purpose of this study is to Constructing of Multidimensional Self-Esteem Scale for individuals within the age range (13-18 years), and to examine its psycho-metric characteristics. It also seeks to investigate variances in dimensions of Self-Esteem based on gender, age and geographic location, The study sample consists of (1008) students of both genders, affiliated with the public schools of the Ministry of Education in Jordan, Grade range of the study sample ranges from 7th Grade to the 12th Grade. The multi-dimensional Self-Esteem Scale has been established after reviewing published scales on trait of Self-Esteem, These scales have been applied to the study sample, Scales have been revised by specialized reviewers, as well Construct Validity indices have been inspected by first factor analyses and Second order factor analyses. Results of Second order factor analyses have shown five main factors including: Academic self-esteem, Family self-esteem, Social self-esteem, Personal self-esteem and peers self-esteem. Criterion-Related validity with Rosenberg self-esteem scale, shows that Pearson correlation coefficient (0.79). Reliability of the scale and its dimension were verified through internal uniformity using Cronbach's alpha coefficient (α) and Split-Half, split-half coefficients corrected by the Spearman Brown formula and Person separation index and item separation index, Reliability values were good range (.64-.81). Multiple analysis of variance (MANOVA) is used to examine differences in the dimension of self-esteem based on variables of gender, age and geographic area at statistical significance (α = 0.05). It shows variances in the dimension of self-esteem, affected by gender tending towards females, with statistical values at significance level of (α= 0.05). This variance was dictated by grade difference from the 7th grade to the 8th grade, in the dimension of academic self-esteem for the 7th grade. Whereas there are variances of statistical values at significance value of (α= 0.05) regarding family, personal, and peers Self-esteem. This variance followed a geographic pattern represented by territory.
Keywords: تقدير الذات -- نظرية الاستجابة للفقرة -- النموذج اللوجستى متعدد الأبعاد ثنائى المعلمة